PERBEDAAN FUNGSI PARU PADA PASIEN USIA LANJUT DENGAN HIPERTENSI DAN TANPA HIPERTENSI DI RSUP DR.SARDJITO YOGYAKARTA (Tinjauan Pustaka dan Laporan Penelitian) - , BUNGSU WAHYU SUTRIANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background. In old age there is a decrease in lung vital capacity to 68%. Intrinsic aging process can develop from metabolic changes such as oxidative stress to the cells. Population of hypertensive patients, especially in the elderly continues to rise. The prevalence of hypertension at the age above 65 years 13% of the population. In the last two decades of research on lung function are the outcome of cardiovascular disease that is often caused by hypertension. Incidence of lung function decline in chronic heart failure and hypertension were found mainly in the elderly. Aims. Knowing the differences in lung function in elderly patients with hypertension and without hypertension Methods. Study is cross-sectional, a study in November 2012 until January 2013. In the elderly population> 60 years of research with a sample of 58 people (29 people and 29 groups of hypertensive people without hypertension). Inclusion criteria for the study subjects were elderly patients over 60 years of signing the informed consent, can perform spirometry maneuvers correctly. Exclusion criteria such as asthma, COPD, chronic heart disease, edema, diabetes mellitus, stroke, musculoskeletal disorders, history of thoracic surgery, history of work exposure to chemical. Then do the history, physical examination, body mass index, blood pressure, electrocardiography and spirometry. Data were analyzed by t test to examine differences in mean / median between the two groups. Results. In this research, the mean gender on hypertension 41.38% male and 58.62% female. In the group without hypertension 13.79% male and 86.21% female (p = 0.038, 95% CI 0.062 to 0.822). ECG results and without hypertension hypertensive group showed more there than without ischemic ischemic (79.31% vs. 20.69% in the hypertensive group